Fetal Mummification In Cow And Its Retention In The Vagina: A Case Report - Kumar, Pramod; Agrawal, J.K.; Verma , Meena (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
Fetal mummification is an abnormal condition in which death of the fetus occurs after mid-gestation, when ossification of the bones has begun and complete resorption of fetal material cannot take place (Noakes et al., 2001). Fetal mummification generally remains unobserved during the first half of pregnancy, because embryonic or fetal death prior to the development of fetal bones usually is followed by unobserved discharge or tissue resorption (Lorenz et al., 2009). The condition has been reported in several species but it is more common in cattle (Roberts, 1971). In the case of haematinic mummification, when the placenta or maternal caruncules regress, a hemorrhage occurs between the endometrium and fetal membranes and, after plasma is reabsorbed, there is a formation of viscous, thick and dark brown tissue, with mucus and clots (Arthur et al., 1996). The present case report describes the retrieval of mummified foetus from the vagina of a cow with history of ten months gestation.